Research Thinking in Medical Profession - Syed Arshad Sabir (Journal of Rawalpindi Medical College, 2021)
Thinking can simply be viewed as, generating your own thoughts on anything, and reviewing these till you comprehend it at some minimum level. Thinking is the most powerful attribute of a human being. In our daily life or even in professional work settings, most of the time our thinking remains limited to others’ ideas or already known facts and it is enough well to carry out our work in a “by default” pattern. While working in a clinical setup we daily confront many disease conditions, and we generally accept and deal with the whole course of illnesses under our memorized knowledge. Our mind is ready to see or accept all pathophysiologic & clinical events of a given disease, management modalities, treatment outcomes, and the complications, as they had been reported or taught and not anything in between. We don’t notice or concentrate on why any variability or difference happening beyond reasons we have learned through our training. This is good enough to run routine practices. But a problem, or a worse happening, costing human suffering or life, need little “thinking” on “why” of it, specifically if it is not explained previously. Actually, any visible variability or event has a set of many underlying sub-events or connections which were linked to eventually produce an apparent happening. The primary act of a researcher’s mind is to notice the varied happening and the job is to theorize its reasons, testify the assumed theory under applicable scientific methods, and infer based on identified facts. Knowledge is floating behind any unexplained thing or such visible phenomenon; it just needs taking notice of it and “thinking” on ‘why & how” of it. Here it would be relevant to recall the saying of a great Nobel laureate Albert Szent-Gyorgyi (medicine 1937) that “Research is to see what everybody else has seen, and to think what nobody else has thought.” This would be the beginning of research thinking. Research thinking is not a one-moment process, rather a start of a chain of connected thoughts which demands more and more reviews and some actions too, till you reach some workable idea or hypothesis. Initially, your thinking may have many intuitive, fictional, or irrational elements but as you move forward, you become more & more pragmatic, and your construct follows scientific rules. Initially, your conceptualized construct may have some ridiculous postulates but actually, you are making efforts towards a way to produce controlled evidence for them. That is the practical pathway of the research. As a matter of fact, it is your intuitiveness or dreaming capacity with which you connect things in a unique or different way to explain a problem or happening which is the real essence of research. Here measures like deep reading on that particular issue, exploring historical purview, talking to fellows, or even conducting small experiments, help a lot to refine and improve your initial theory or construct. “I find for myself that my first thought is never my best thought. My first thought is always someone else’s; it’s always what I’ve already heard about the subject, always the conventional wisdom. It is only by concentrating, sticking to the question, being patient, letting all the parts of my mind come into play, that I arrive at an original idea. By giving my brain chances to make associations, draw connections, take me by surprise”. And often even that idea doesn’t turn out to be very good. I need time to think about it, too, to make mistakes and recognize them, to make false starts and correct them, to outlast my impulses, to defeat my desire to declare the job done and move on to the next thing. You do your best thinking by slowing down and concentrating. The best way to improve your ability to think is to spend time thinking.